2014
DOI: 10.1111/cch.12211
|View full text |Cite
|
Sign up to set email alerts
|

The association between family factors and child behaviour problems using dyadic data

Abstract: The findings indicated that paternal psychopathology and family functioning should not be overlooked in child behaviour development. In addition, this study underscored the importance to investigate the different impact of father and mother on child development within a dyadic unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…Healthy FF was related to better MH outcomes, following ACEs and conversely, poor FF was related to poorer MH outcomes following ACEs. There were differences between studies depending on whether it was the mother or the father of the child who was reporting on FF and parental MH problems (Burstein et al , ; Wang et al , ). Five of the studies which reported this association reported on differences in specific aspects of FF which did or did not mediate the relationship between ACEs and MH (Breaux et al , ; Burstein et al , ; Li et al , ; Platt et al , ; Wang et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthy FF was related to better MH outcomes, following ACEs and conversely, poor FF was related to poorer MH outcomes following ACEs. There were differences between studies depending on whether it was the mother or the father of the child who was reporting on FF and parental MH problems (Burstein et al , ; Wang et al , ). Five of the studies which reported this association reported on differences in specific aspects of FF which did or did not mediate the relationship between ACEs and MH (Breaux et al , ; Burstein et al , ; Li et al , ; Platt et al , ; Wang et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…There were differences between studies depending on whether it was the mother or the father of the child who was reporting on FF and parental MH problems (Burstein et al , ; Wang et al , ). Five of the studies which reported this association reported on differences in specific aspects of FF which did or did not mediate the relationship between ACEs and MH (Breaux et al , ; Burstein et al , ; Li et al , ; Platt et al , ; Wang et al , ). For example, Li and colleagues (2017) reported that among children with oppositional defiant disorder (ODD), the parent‐child relationship mediated the relationship between physical abuse and anger management, but not aggressive behaviour.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted to understand the relationship amongst family functioning, parental depression, and child behavior problems, Wang et al 49 found that only paternal perception of family functionally mediates the relation between parental depression and child behavior, and fathers' depression may influence child behavior problems. Additionally, when considered mothers and fathers together, their depression may influence each other and their spouses' perceived family.…”
Section: Discussionmentioning
confidence: 99%
“…Os estudos sobre o tema buscam compreender as associações entre o funcionamento familiar e os problemas de comportamento das crianças (Ma, Yao & Zhao, 2013). Os autores sugerem que existe uma relação bidirecional entre as variáveis funcionamento familiar, psicopatologia parental (depressão e abuso de álcool) e problemas de comportamento entre as crianças (Wang, Pan, Zhang & Yi, 2014;Burstein, Stanger & Dumenci, 2012). Lamela e Figueiredo (2016) avaliaram se o estado civil dos pais tinha influenciado a saúde mental das crianças e observaram que pais divorciados, que apresentaram mais sintomas de depressão, usaram mais punição física e estes fatores foram correlacionados com maior prejuízo para a saúde mental das crianças.…”
Section: Introductionunclassified